Experimental and Numerical Studies on Permeability Properties of Thermal Damaged Red Sandstone under Different Confining Pressures. (24th February 2021) - Zhao, Zhenlong; Jing, Hongwen; Fu, Guangping; Yin, Qian; Shi, Xinshuai; Gao, Yuan
Abstract : The stability and safety of underground rock mass engineering are closely related to the permeability process of fluids and permeability properties of rocks. To reveal the flow behavior of fluid in thermal damaged rock, first, a rock seepage testing system was applied to study the permeability properties of red sandstone specimens after different high-temperature treatments from 200 to 800°C under different confining pressures of 10 to 30 MPa. Meanwhile, the microstructures of the red sandstone specimens were characterized by the mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM). Then, the permeability process of pore water pressure and the flow form of fluid also were investigated by the numerical modeling method. The results show that the permeability properties of red sandstone specimens after high-temperature exposure follow linear Darcy's law, and the relation between confining pressures and equivalent permeability coefficient (K 0 ) can be described by a power function. Besides, the phenomenon that microscopic structural deterioration is intensified with increasing temperature and the average pore size and porosity of the red sandstone specimens are both power functions is related to the equivalent permeability coefficient. Furthermore, the results of numerical modeling indicated that the flow field within the range affected by confining pressures gradually becomes stable and orderly from disorder, and flow lines of the fluid become smooth and straight, and perpendicular to the isosurface of pore water pressure as time goes by. Moreover, the nonlinear correlation between pore water pressure and seepage path length changes to a linear correlation, which is consistent with linear Darcy's law.